Simulation of Turbulent Flows with and without Combustion with Emphasis on the Impact of Coherent Structures on the Turbulent Mixing - Cunha Galeazzo, Flavio Cesar (KIT Scientific Publishing, 2016)
The analysis of turbulent mixing in complex turbulent flows is a challenging task. The effective mixing of entrained fluids to a molecular level is a vital part of the dynamics of turbulent flows, especially when combustion is involved. The work has shown the limitations of the steady-state simulations and acknowledged the need of applying high-fidelity unsteady methods for the calculation of flows with pronounced unsteadiness promoted by large-scale coherent structures or other sources.